Substrate-Induced Allosteric Change in the Quaternary Structure of the Spermidine N-Acetyltransferase SpeG. Issue 22 (6th November 2015) - Filippova, Ekaterina V.; Weigand, Steven; Osipiuk, Jerzy; Kiryukhina, Olga; Joachimiak, Andrzej; Anderson, Wayne F.
Abstract: The spermidine N -acetyltransferase SpeG is a dodecameric enzyme that catalyzes the transfer of an acetyl group from acetyl coenzyme A to polyamines such as spermidine and spermine. SpeG has an allosteric polyamine-binding site and acetylating polyamines regulate their intracellular concentrations. The structures of SpeG from Vibrio cholerae in complexes with polyamines and cofactor have been characterized earlier. Here, we present the dodecameric structure of SpeG from V. cholerae in a ligand-free form in three different conformational states: open, intermediate and closed. All structures were crystallized in C 2 space group symmetry and contain six monomers in the asymmetric unit cell. Two hexamers related by crystallographic 2-fold symmetry form the SpeG dodecamer. The open and intermediate states have a unique open dodecameric ring. This SpeG dodecamer is asymmetric except for the one 2-fold axis and is unlike any known dodecameric structure. Using a fluorescence thermal shift assay, size-exclusion chromatography with multi-angle light scattering, small-angle X-ray scattering analysis, negative-stain electron microscopy and structural analysis, we demonstrate that this unique open dodecameric state exists in solution. Our combined results indicate that polyamines trigger conformational changes and induce the symmetric closed dodecameric state of the protein when they bind to their allosteric sites. Graphical abstract: Highlights: Spermidine N -acetyltransferase (SpeG) in ligand-free form has multiple oligomeric forms in solution. SpeG structure revealed a unique open dodecameric state. Polyamine alters a shift from the asymmetric open state to the closed symmetric dodecameric state.